HOLDING EMPLOYEE DIPLOMAS: LEGAL IMPLICATIONS AND WORKERS' RIGHTS CONCERNS - Indarta, Didiek Wahju; Mutmainah, Lailatul; Rahmania, Cindy Swastika (Jurnal Al-Dustur, 2025)
The detention of diplomas is carried out under the pretext that employees do not resign before the contract period ends. However, this action raises legal problems because it has the potential to violate the basic rights of workers, especially the right to private property and freedom of work. This is because every individual has the constitutional right to maintain ownership of the assets he or she legally acquires, including the results of work or income that are part of his or her personal property. If the policies or actions of the company, the government, or other parties limit or even confiscate part of the property without a clear and fair legal basis, then this can be considered a violation of the principle of non-deprivation of property without due process. This study aims to examine the practice of diploma retention from the perspective of employment law based on Law Number 13 of 2003 concerning Manpower, as well as examine its legal implications for companies and workers. The research method used is normative juridical, with a legislative approach. The results of the study show that there is no strict provision in Law Number 13 of 2003 that allows the retention of diplomas by companies. On the contrary, the practice is contrary to the principle of protection of workers' rights regulated in the law and contrary to the principles of legal certainty and justice. Workers have the right to be actively involved in the process of drafting employment agreements through joint deliberation with employers, as stipulated in Article 52 of the Manpower Law. Diploma detention can be categorized as a form of violation of the law and the company can be subject to administrative or criminal sanctions if proven to be detrimental to workers. To overcome this, stronger and integrated law enforcement mechanisms are also needed, such as increasing the capacity and authority of labor supervisors, the establishment of special units to deal with violations of workers' rights, and the application of strict administrative and criminal sanctions against violating companies.